Power quality in Power Supply Systems study aid - Shanenkov, I. I. specialist in the field of electric power engineering Associate Professor of the Department of Tomsk Polytechnic University, Candidate of Sciences 1990- (TPU Publishing House, 2021)
The textbook covers questions on the power quality (PQ) in the power supply systems studied within the course "Power quality in power supply systems". There are given: the analysis of main causes and sources of interference worsening the power quality indices (PQI) and leading to the normal functioning disruption of power supply systems; the examples of consequences when the current-consuming devices operate with PQI deviations from the standard ones; the information on improving the quality indices to the level of electromagnetic compatibility of power supply facilities.